Benefits of pattern formation by severe plastic deformation. (June 2019) - Kulagin, R.; Beygelzimer, Y.; Bachmaier, A.; Pippan, R.; Estrin, Y.
Graphical abstract: Highlights: SPD induces structural and compositional patterning in composites. Patterned materials exhibit exceptional properties. Micromanufacturing was identified as a promising field where patterned materials can be applied. Abstract: Nature abounds with patterns of various kinds. Possible cellular, helical, wavy, fold-like, fractal, and other structures provide natural objects with distinctive, and often unique, physico-mechanical properties. This has motivated many researchers to turn to nature in their quest for engineered advanced materials. The present article aims at demonstrating the outstanding potential of severe plastic deformation (SPD) processing for creating various spatial patterns in the structure of metallic composites. Two pathways for patterning are considered: (i) bifurcations under plastic flow, including shear banding, folding, and periodic vortex formation, and (ii) self-organisation caused by heterogeneous chemical reactions in a plastically deforming medium. The article concludes by a demonstration of the prospects for the use of materials with SPD-induced structural and compositional patterns in the burgeoning area of micromanufacturing.